PENGARUH PENAMBAHAN MINERAL Fe PADA PAKAN IKAN TERHADAP STATUS KESEHATAN IKAN KERAPU BEBEK (Cromileptes aftivelis) - Setiawati, Mia; Mokoginta, Ing; Suprayudi, M.A.; Manalu, W. (Jurnal Perikanan dan Kelautan, 2007)
This study was conducted to find out the health status of humpback grouper fish(('hrtmtileptes altiverts) that are fed on inorganic-iron supplement. Both, thetreatment and the control was tested in anoxia condition. The fish (average weight4.18±0.13 g/ind) was cultured in 60x40x50 cm3 aquarium and stocked by 10indJaquarium. The fish was reared for 10 weeks: and they were fed threetimes/day at satiation. Results shown that the fish fed by non-iron supplement wasmore susceptible than the normal condition; base on the index of leucocytes,nionocytes. phagocytic and MCHC distribution. However, 25 mg Fe/kgsupplement in the diet was increased concentration of Fe by 35% - 100% in liver,intestine, body tissue and enhance fish vitality at anoxia condition. The survivalrate of fish increased by 1.3 times compare to the non-iron supplementation.